Industry and Occupation Variations in Nonmedical Prescription Pain Reliever Use - Cluff, L.; Tueller, S.; Batts, K.; Miller, Ted; Galvin, D. (2014)
© 2014, Taylor & Francis Group, LLC. Nonmedical use of prescription pain relievers can be a serious problem for employers. Despite growing attention to prescription drug abuse, little is known about which industries or occupations are at the highest risk for misuse. This study used data from the National Survey on Drug Use and Health to compare each industry to every other industry to identify significant differences in rates of past-year prescription drug misuse. Findings suggest that for industries with the highest prevalence rates, prescription misuse cannot be explained by basic demographics and likely involves elements inherent to the work context and requirements.